The effect of CPT-1 inhibition on myocardial function and resistance to ischemia/reperfusion injury in a rodent model of the metabolic syndrome - Maarman, Gerald Jerome (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Dept. of Biomedical Sciences. Medical Physiology))University of Stellenbosch, 2010.